2018
DOI: 10.1002/gps.4841
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cognitive decline and dementia in rural areas — A scoping review

Abstract: Telehealth applications can appropriately be used to diagnose dementia. However, most of the studies included only small sample sizes and did not test the applications explicitly in rural or remote populations. Therefore, studies taking these limitations into account are needed. On top, only two RCTs are included in this review indicating that more high quality studies in this field are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
(131 reference statements)
0
19
0
5
Order By: Relevance
“…In addition, the rural residence setting could have remoteness due to the low population density. It could aggravate withdrawal from community (Barth, Nickel, & Kolominsky‐Rabas, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rural residence setting could have remoteness due to the low population density. It could aggravate withdrawal from community (Barth, Nickel, & Kolominsky‐Rabas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Health practitioners have used TM to diagnose dementia in older people who cannot attend or travel long distances for assessment. Studies have found that TM can be as accurate as face-to-face (FTF) diagnosis, with similar levels of patient satisfaction (Barth, Nickel, & Kolominsky-Rabas, 2018;Martin-Khan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Barth et al untersuchten in ihrer Übersichtsarbeit Interventionen zur Früherkennung des Abbaus kognitiver Fähigkeiten und zur Diagnosestellung bei Demenz in ländlichen Regionen [16]. Der begrenzte Zugang zu Demenz-Abklärung bzw.…”
Section: Wie Kann Früherkennung Und Diagnosestellung Von Demenz In Läunclassified